Analisis Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi Keanekaragaman Hayati di Kelas X - Stivani, Elly; Djulia, Ely; Hasairin, Ashar (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the students' higher order thinking skills on biodiversity material in class X. This research uses a quantitative descriptive approach. The sample of this study was class X students consisting of 104 people determined by cluster random sampling technique. The instrument used was a test question in the form of an essay of 12 items on biodiversity material. The results showed that students' higher order thinking skills on biodiversity material in class X were at very low criteria with the acquisition of an average student score of 44.5%. In each indicator, it was found that the C4 indicator of class X students was very low with a percentage of 44.3%, the C5 indicator was very low with a percentage of 40.0%, and the C6 indicator was very low with a percentage of 46.0%. Thus, it can be concluded that to be able to improve the higher order thinking skills of grade X students, students begin to familiarize themselves with reading various literatures, solve HOTS-based problems, and students must use various learning strategies.